Multi-Criteria Analysis for Geospatialization of Potential Areas for Water Reuse in Irrigated Agriculture in Hydrographic Regions - Ana Paula Pereira Carvalho; Ana Claudia Pereira Carvalho; Mirian Yasmine Krauspenhar Niz; Fabrício Rossi; Giovana Tommaso; Tamara Maria Gomes (Agronomy)
As the climate crisis progresses, droughts and the seasonal availability of fresh water are becoming increasingly common in different regions of the world. One solution to tackle this problem is the reuse of treated wastewater in agriculture. This study was carried out in two significant hydrographic regions located in the southeast of Brazil (Mogi Guaçu River Water Management Unit—UGRHI-09 and Piracicaba River Basin—PRB) that have notable differences in terms of land use and land cover. The aim of this study was to carry out a multi-criteria analysis of a set of environmental attributes in order to classify the areas under study according to their levels of soil suitability and runoff potential. The integrated analysis made it possible to geospatialize prospective regions for reuse, under two specified conditions. In the UGRHI-09, condition 1 corresponds to 3373.24 km2, while condition 2 comprises 286.07 km2, located mainly in the north-western and central-eastern portions of the unit. In the PRB, condition 1 was also more expressive in occupational terms, corresponding to 1447.83 km2; and condition 2 was perceptible in 53.11 km2, predominantly in the central region of the basin. The physical characteristics of the areas studied were decisive in delimiting the areas suitable for the reuse of treated wastewater.